2017
DOI: 10.1111/dom.13167
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of clozapine‐associated obesity and diabetes with exenatide in adults with schizophrenia: A randomized controlled trial (CODEX)

Abstract: Clozapine causes obesity and type 2 diabetes (T2DM). Glucagon-like peptide-1 (GLP-1) receptor agonists (e.g. exenatide) can counter clozapine-associated GLP-1 dysregulation in animals, and may be beneficial in people on clozapine. This randomized, controlled, open-label, pilot trial evaluated weekly exenatide for weight loss among clozapine-treated obese adults with schizophrenia, with or without T2DM. A total of 28 outpatients were randomized to once-weekly extended-release subcutaneous exenatide or usual car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 17 publications
0
63
0
1
Order By: Relevance
“…Although schizophrenia is typically associated with the greatest degree of cardiovascular risk (partly due to the side-effects of antipsychotic medications), there is now compelling evidence that obesity, metabolic syndrome, diabetes and cardiometabolic disease are similarly elevated in other mental disorders, including CMDs. [26][27][28][29][66][67][68][69][70][71][72][73] Given the higher prevalence of these mental disorders across the population, developing transdiagnostically-applicable strategies for improving cardiometabolic health outcomes in these populations (along with SMIs) could considerably reduce the premature mortality and lifelong burden of poor physical health which affects people with mental illness across the globe. Within this, the impact and prevalence of other NCDs and infectious diseases, in both high income and LMIC setting, cannot be neglected.…”
Section: Further Considerations On Physical-mental Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although schizophrenia is typically associated with the greatest degree of cardiovascular risk (partly due to the side-effects of antipsychotic medications), there is now compelling evidence that obesity, metabolic syndrome, diabetes and cardiometabolic disease are similarly elevated in other mental disorders, including CMDs. [26][27][28][29][66][67][68][69][70][71][72][73] Given the higher prevalence of these mental disorders across the population, developing transdiagnostically-applicable strategies for improving cardiometabolic health outcomes in these populations (along with SMIs) could considerably reduce the premature mortality and lifelong burden of poor physical health which affects people with mental illness across the globe. Within this, the impact and prevalence of other NCDs and infectious diseases, in both high income and LMIC setting, cannot be neglected.…”
Section: Further Considerations On Physical-mental Comorbiditiesmentioning
confidence: 99%
“…Part 1 identified cardiometabolic diseases as a category of physical comorbidities that are particularly pervasive and impactful on well-being, morbidity and mortality, across many mental disorders. [26][27][28][29][55][56][57][66][67][68][69][70][71][72][73]82 Along with side-effects of psychotropic medications (covered in Part 3), reasons for the increased cardiometabolic morbidity and mortality in people with mental illness can be divided into patient-related and provider/system-level factors. 25 Clear modifiable patient-related factors known to heavily influence cardiometabolic diseases are 'lifestyle risk factors' such as smoking, poor diet, and inactivity 35,[83][84][85] ; adverse health behaviours which also influence many other aspects of physical health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other randomized clinical trials also evaluated a GLP-1RA, exenatide 2 mg s.c. onceweekly, in patients with schizophrenia or schizo-affective disorder treated either with clozapine (40,41) or a mixture of antipsychotics (41)(42)(43). One study showed a significant weight reduction of 5.3 kg in the treatment group vs. 1.1 kg in the placebo group (P = 0.02) (40), while the other one did not show any difference (2.2 kg in the treatment group vs. 2.2 kg in the placebo group, P = 0.98) (42,43). However, to what degree the statistically significant and clinically meaningful improvements observed during active liraglutide treatment are sustained after liraglutide is stopped is unknown.…”
Section: Accepted Articlementioning
confidence: 99%
“…Patients treated with antipsychotic medications are known to have a reduced life-expectancy mainly due to cardiovascular disease (16), and therefore GLP-1RAs could offer an attractive new treatment option. While liraglutide is administered as a once-daily injection, which may limit the compliance and widespread use in clinical practise, several once-weekly GLP-1RAs are already on the market, which might be more suitable for psychiatric patients instead of daily injections (40,59).…”
Section: Accepted Articlementioning
confidence: 99%